Improved method for the experimental determination of in-medium effects from heavy-ion collisions. (14th September 2020) - Pais, Helena; Bougault, Rémi; Gulminelli, Francesca; Providência, Constança; Bonnet, Eric; Borderie, Bernard; Chbihi, Abdelouahad; Frankland, John D; Galichet, Emmanuelle; Gruyer, Diégo; Henri, Maxime; Neindre, Nicolas Le; et al.
Abstract: The equation of state with light clusters for nuclear and stellar matter is determined using chemical equilibrium constants evaluated from the analysis of the recently published (Xe + Sn) heavy ion data, corresponding to three reactions with different isotopic contents of the emission source. The measured multiplicities are used to extract the thermodynamic properties, and an in-medium correction to the ideal gas internal partition function of the clusters is included in the analysis. This in-medium correction and its respective uncertainty are calculated via a Bayesian analysis, with the unique hypothesis that the different nuclear species in a given sample must correspond to a unique common value for the density of the expanding source. Different parameter sets for the correction are tested, and the effect of the radius of the clusters on the thermodynamics and on the chemical equilibrium constants is also addressed. It is shown that the equilibrium constants obtained are almost independent of the isospin content of the analysed systems. Finally, a comparison with a relativistic mean field model proves that data are consistent with a universal in-medium correction of the scalar σ -meson coupling for nucleons bound in clusters. The obtained value, g s / g s 0 = 0.92 ± 0.02, is larger than that obtained in a previous study not including in-medium effects in the data analysis. This result implies a smaller effect on the binding energy of the clusters and, as a consequence, larger melting densities, and an increased cluster contribution in supernova matter.